2005
DOI: 10.1111/j.1601-5037.2005.00121.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal disease awareness among pregnant women and its relationship with socio‐demographic variables

Abstract: Certain conditions may have an affect on gingival status and may aggravate pre-existing disease, especially in persons with poor oral hygiene. Pregnancy is one of these conditions. In addition, there is evidence in the literature suggesting an association between periodontal diseases in pregnant women and giving birth to premature, low-birth infants. The purpose of this study was to evaluate the degree of periodontal health knowledge, and awareness, among pregnant women in Jordan. This was carried out by cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
30
2
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 13 publications
8
30
2
4
Order By: Relevance
“…Conclusions of almost all those authors have formed a general message that pregnant women should be classified as a dentally vulnerable group in the countries that do not respect the rule yet, and that the range of prevention activities in the countries that already comply with this rule should be expanded [6,19,21,22]. Current self-assessment is the primary motivator for pregnant women to undertake or refrain from taking numerous important steps, such as urgent visit to a dentist, starting the thorough cleaning of the teeth, use of dental floss or rinsing oral cavity with a rinsing liquid, or including products containing fluoride into the diet, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conclusions of almost all those authors have formed a general message that pregnant women should be classified as a dentally vulnerable group in the countries that do not respect the rule yet, and that the range of prevention activities in the countries that already comply with this rule should be expanded [6,19,21,22]. Current self-assessment is the primary motivator for pregnant women to undertake or refrain from taking numerous important steps, such as urgent visit to a dentist, starting the thorough cleaning of the teeth, use of dental floss or rinsing oral cavity with a rinsing liquid, or including products containing fluoride into the diet, etc.…”
Section: Discussionmentioning
confidence: 99%
“…If this change is accompanied by a lack of concern for oral hygiene, plaque and multiplying microorganisms may cause gingivitis and periodontitis. Periodontal diseases are listed as one of the causes of pre-term birth or low birth weight [2,5,6]. Growth of pathogenic oral flora is enhanced by unhealthy dietary habits: increased intake of simple sugars as well as higher frequency of intake of snacks between the main meals.…”
Section: Methodsmentioning
confidence: 99%
“…A study carried out by Alwaeli and AlJundi (21) noted that only 5.1% of preg nant respondents believed there might be a relationship be tween gum diseases and premature labour. However, 56% of pregnant respondents did not believe that the frequency of teeth brushing should be increased during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that pregnant women needed more ac curate and complete information about their teeth and oral health. Moreover, simple educational preventive programs on oral selfcare and disease prevention before and during pregnancy should be provided to improve oral health (21). A research carried out by K. Dinas et al showed that the majority of pregnant women (72.2%) believed that dental treatment during pregnancy might have a negative effect on pregnancy outcome (9).…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy also contributes to tumor-like growths, epulisgravidarum (0.2% to 9.6% of pregnant patients), care practices in some manner influence periodontal disease outcomes in pregnant women as well as their offspring [21,22].…”
Section: Introductionmentioning
confidence: 99%